2022
DOI: 10.1186/s13073-022-01076-0
|View full text |Cite
|
Sign up to set email alerts
|

High fluoroquinolone resistance proportions among multidrug-resistant tuberculosis driven by dominant L2 Mycobacterium tuberculosis clones in the Mumbai Metropolitan Region

Abstract: Background Multidrug-resistant (MDR) Mycobacterium tuberculosis complex (MTBC) strains are a serious health problem in India, also contributing to one-fourth of the global MDR tuberculosis (TB) burden. About 36% of the MDR MTBC strains are reported fluoroquinolone (FQ) resistant leading to high pre-extensively drug-resistant (pre-XDR) and XDR-TB (further resistance against bedaquiline and/or linezolid) rates. Still, factors driving the MDR/pre-XDR epidemic in India are not well defined. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 54 publications
1
14
0
Order By: Relevance
“…In this study, 16.56% (26/157) of Multidrug-resistant tuberculosis isolates and 4.02% (20/498) isoniazid-resistant are fluoroquinolone-resistant, a characteristic distribution leading to about 17.2% of fluoroquinolone resistance events and relevant marker gyr-A mutations in MDR tuberculosis isolates. Dreyer et al [40] reported 69.2% (703/1016) fluoroquinolone resistance among 1016 Multidrug-resistant tuberculosis isolates tested for resistance. In India, 36% of the Multidrugresistant tuberculosis isolates are browned to have additional resistance to fluoroquinolone [41,42], and about 3% of MDR-TB isolates are estimated to have extensively drug-resistant (XDR-TB).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, 16.56% (26/157) of Multidrug-resistant tuberculosis isolates and 4.02% (20/498) isoniazid-resistant are fluoroquinolone-resistant, a characteristic distribution leading to about 17.2% of fluoroquinolone resistance events and relevant marker gyr-A mutations in MDR tuberculosis isolates. Dreyer et al [40] reported 69.2% (703/1016) fluoroquinolone resistance among 1016 Multidrug-resistant tuberculosis isolates tested for resistance. In India, 36% of the Multidrugresistant tuberculosis isolates are browned to have additional resistance to fluoroquinolone [41,42], and about 3% of MDR-TB isolates are estimated to have extensively drug-resistant (XDR-TB).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, 16.56% (26/157) of multidrug-resistant tuberculosis isolates and 4.02% (20/498) isoniazid-resistant are fluoroquinolone-resistant, a characteristic distribution leading to about 17.2% of fluoroquinolone resistance events and relevant marker gyr-A mutations in MDR tuberculosis isolates. Dreyer et al [44] reported 69.2% (703/1016) fluoroquinolone resistance among 1016 multidrug-resistant tuberculosis isolates tested for resistance. In India, 36% of the multidrug-resistant tuberculosis isolates are browned to have additional resistance to fluoroquinolone [45,46], and about 3% of MDR-TB isolates are estimated to be extensively drug-resistant (XDR-TB).…”
Section: Discussionmentioning
confidence: 99%
“…M. Tuberculosis data is publicly available under Accession ID PRJEB41116 (18). SARS-CoV-2 data is publicly available under Accession ID PRJNA817806 (6).…”
Section: Data Availabilitymentioning
confidence: 99%
“…We tested the generality of OASIS-opt's inferential power to classify microbial variants in a different microorganism, the bacterium M. Tuberculosis. We processed data from 25 isolates from two subsublineages known to derive from the sublineage 3.1: 3.1.1 and 3.1.2 (Accession ID PRJEB41116 (19)). Currently, bacterial typing is based on manual curation and SNPs, is highly manually intensive, and requires mapping to a reference genome.…”
Section: M Tuberculosis Strain Identificationmentioning
confidence: 99%